2021
DOI: 10.31635/ccschem.020.202000350
|View full text |Cite
|
Sign up to set email alerts
|

Positive/Negative Phototropism: Controllable Molecular Actuators with Different Bending Behavior

Abstract: Herein, a series of molecular actuators based on the crystals of (E)-2-(4-fluorostyryl)benzo[d]oxazole (BOAF4), (E)-2-(2,4-difluorostyryl)benzo[d]oxazole (BOAF24), (E)-2-(4-fluorostyryl)benzo[d]thiazole (BTAF4), and (E)-2-(2,4-difluorostyryl)benzo[d]thiazole (BTAF24) showed unique bending behavior under UV irradiation. The one-dimensional (1D) crystals of BOAF4 and BTAF4 bent toward light, whereas those of BOAF24 and BTAF24 bent away from light.Although the chemical structures of these compounds are similar, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…Wang et al reported [29] another elegant work through the fluorine derivatives of styrylbenzoxazoles and styrylbenzothiazoles, keeping in view of the possible effect on the topophotochemical reaction. In this regard, (E)-2-(4-fluorostyryl) benzo [d] 26) compounds have been prepared.…”
Section: Mechanical Motion In Organic Crystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al reported [29] another elegant work through the fluorine derivatives of styrylbenzoxazoles and styrylbenzothiazoles, keeping in view of the possible effect on the topophotochemical reaction. In this regard, (E)-2-(4-fluorostyryl) benzo [d] 26) compounds have been prepared.…”
Section: Mechanical Motion In Organic Crystalsmentioning
confidence: 99%
“…The significant role of halogens has been observed to be used as steering groups in arranging π-systems, which advocated that halogens can be judiciously applied as an useful ''crystal engineering'' group for inducing mechanical motion during topochemical reactions. [28,29] With regard to this, few more examples were found to exhibit light-induced curling, flipping, bending, bursting, coiling, twisting and cracking in the dynamic molecular crystals of halogen-substituted naphthalene acrylic acids developed by Lu and worker. 30 Stereospecific [2 + 2] cycloaddition reactions have been shown by (E)-3-(1fluoronaphthalen-2-yl)acrylic acid (1FNaAA) (27); (E)-3-(1-chloronaphthalen-2-yl)acrylic acid (1ClNaAA), (28); (E)-3-(1-bromonaphthalen-2-yl)acrylic acid (1BrNaAA), ( 29), (E)-3-(1-iodonaphthalen-2-yl)acrylic acid (1INaAA) (30), (E)-3-(6-bromonaphthalen-2-yl)acrylic acid, (6BrNaAA) (31).…”
Section: Mechanical Motion In Organic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the importance of light for life. [ 2 ] Inspired by the light‐responsive properties that occur naturally, various intelligent photoresponsive materials have been developed in recent years, such as molecular actuator, [ 3 ] artificial muscles, [ 4‐5 ] and artificial synapses. [ 6 ] In fact, the reason for the popularity of light‐responsive materials is that, among various external stimuli, [ 7‐8 ] light shows unique advantages, including remote activation, space‐ controlled activation, facile switch process, and the miniaturization of devices.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…16,26 From this consideration, organic aggregates showing the AIE effect are also promising to provide a new insight on pursuing white-light emission in terms of strategies and applications. [27][28][29] Some luminogens with the AIE effect (AIEgens) with flexible structures can emit polychromatic colors simultaneously in the aggregate state, achieving the requirements for white light. In addition, the solid-state form and high efficiency of AIEgens are beneficial to practical applications.…”
Section: Introductionmentioning
confidence: 99%